Proceso de atención de enfermería aplicado en una embarazada de 32 semanas de gestación con amenaza de parto pretermino - Nuñez Castro, Karen Andrea (2018)
Preterm delivery is delivery that occurs after week 20 and before the 37 full weeks accompanied by uterine contractions with a frequency of 1 in 10 minutes, 30 seconds in duration with 50% neck erasure and equal dilation or less than 3 cms. Despite advances in obstetric care, this incidence has not decreased in recent years, and in some countries the tendency is to increase, appearing as the cause of death in 60-80% of newborns without malformations. The threat of preterm delivery may have a multifactorial origin. In most cases, we do not know the triggering cause. Other times, there is a more or less obvious reason (multiple gestation) that explains the appearance of the dynamics. At other times, we can identify infectious factors from other foci of the organism. But up to 13%, there is an infection / inflammation triggering the picture. Given that the literature reports an increase in neonatal morbidity secondary to this infectious process and an increased risk of preterm delivery, the identification of this etiology could have a relevant importance to improve the overall prognosis of pregnancy in these cases. Evidence of this is the presentation of cases considered one of the practical methods for development and training, which corresponds to the description of the process of care performed to a patient, from its assessment to the evaluation of its results and the logical process itself in the decision-making during care, thus becoming a learning approach that allows to unfold and enrich the cognitive process of nursing in practical practical functions; as the fulfillment of the pharmacological treatment, emotional support in search of the recovery or maintenance of the health of the individual, family or community in our care